LAMBL’S EXCRESCENCES AS RISK FACTOR OF CARDIOVASCULAR DISORDERS PARTICULARLY ISCHEMIA WITH NON-OBSTRUCTIVE CORONARY ARTERIES - Lizogub, V.G.; Savchenko, O.V.; Tyravska, Yu.V.; Nadeem, T.; Sobol, V.O.; Kramarova, V.N. (World of Medicine and Biology, 2024)
The purpose of the study was to observe the patients with Lambl’s excrescences and to reveal the principal complaints and primary cardiovascular diagnosis in this cohort. We paid special attention to possible pathogenetic links of ischemia with non-obstructive coronary arteries which were provoked by Lambl’s excrescences with intracardial thrombi and phenomena of hyperechogenicity in the current group. All patients with registered echocardiography Lambl’s excrescences underwent anamnesis taking, physical examination, and 24-hours Holter monitoring. As substantiation of our survey one case of Lambl’s excrescences with intracardial microthrombi in a young female patient with ischemia with non-obstructive coronary arteries was elucidated in current manuscript. It was highlighted the importance of microrheological changes as a paramount link in patients with cardiovascular disorders. Mindful pathogenetic-oriented treatment was discussed for optimization of the patients’ management. The article arises the awareness of the scientific community regarding Lambl’s excrescences as risk factor of quite common cardiovascular disorders.